2017
DOI: 10.1523/jneurosci.3377-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Ventrolateral Striatal Medium Spiny Neurons Positively Regulate Food-Incentive, Goal-Directed Behavior Independently of D1 and D2 Selectivity

Abstract: The ventral striatum is involved in motivated behavior. Akin to the dorsal striatum, the ventral striatum contains two parallel pathways: the striatomesencephalic pathway consisting of dopamine receptor Type 1-expressing medium spiny neurons (D1-MSNs) and the striatopallidal pathway consisting of D2-MSNs. These two genetically identified pathways are thought to encode opposing functions in motivated behavior. It has also been reported that D1/D2 genetic selectivity is not attributed to the anatomical discrimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
141
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 102 publications
(155 citation statements)
references
References 36 publications
(23 reference statements)
12
141
2
Order By: Relevance
“…Fiber photometry recordings of SPNs in the NAc and dorsal striatum also showed large transients of calcium concentrations time locked to cues and specific behaviors during behavioral tasks (Calipari et al, 2016; Cui et al, 2014; Natsubori et al, 2017; Zalocusky et al, 2016), suggestive of population synchrony during actions, though again not necessarily due to cells in close proximity. Moreover, deep brain calcium imaging, which provides a wide field of view, shows clusters of SPNs that display synchronized calcium transients during free locomotion.…”
Section: Spn Collateral Transmission Drives Lateral Inhibitionmentioning
confidence: 95%
See 3 more Smart Citations
“…Fiber photometry recordings of SPNs in the NAc and dorsal striatum also showed large transients of calcium concentrations time locked to cues and specific behaviors during behavioral tasks (Calipari et al, 2016; Cui et al, 2014; Natsubori et al, 2017; Zalocusky et al, 2016), suggestive of population synchrony during actions, though again not necessarily due to cells in close proximity. Moreover, deep brain calcium imaging, which provides a wide field of view, shows clusters of SPNs that display synchronized calcium transients during free locomotion.…”
Section: Spn Collateral Transmission Drives Lateral Inhibitionmentioning
confidence: 95%
“…Extending this idea to the ventral striatum, optogenetic inhibition of either iSPN or dSPNs in the NAc after trial start cue in an operant food task reduced motivated responding on the task (Natsubori et al, 2017), and inhibiting synaptic transmission from either iSPNs or dSPNs prevents the acute locomotor response to cocaine and methamphetamine, a behavior known to involve the NAc (Hikida et al, 2010). These studies provide evidence that both dSPNs and iSPNs are more active during actions than at rest, and activity in both SPN subtypes is needed for driving normal motivated behavior.…”
Section: General Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, these increased responses to drug-associated contextual cues by D1 MSNs were still present after a 2-week withdrawal period, suggesting that the changes in the population activity were stable and long-lasting (Calipari et al, 2016). This is particularly interesting because recent work with food self-administration has shown that both D1 and D2 MSN activity is stimulated, suggesting that something is fundamentally different about the encoding of food and drug rewards (Natsubori et al, 2017). …”
Section: The Neural Circuits Controlling Motivated Behaviors and Thmentioning
confidence: 99%